Microwave-free nuclear magnetic resonance at molecular scales - James D. A. Wood (Nature Portfolio, 2017)
Nitrogen vacancy centres can be used for nanoscale nuclear magnetic resonance detection but this typically involves strong microwave control pulses, making practical realizations difficult. Here the authors demonstrate a microwave-free spectroscopic protocol that can detect spins in external samples.